Knowledge, attitude and practices of intestinal helminths and protozoa infection among parents of school children in peripheral school and urban school area in Kuantan, Pahang, Malaysia - Mat Yusof, Afzan; Md Isa, Muhammad Lokman (Experimental, Biotechnological, Clinical and Strategic Health Research Association, Turkey, 2017)
Intestinal helminths and intestinal protozoa infections are one of the leading causes of diseases among young people and adults in the world today. Ascaris lumbricoides (A. lumbricoides) and Trichuris trichiura (T. trichiura) are the most common intestinal helminths infected people especially among children. Various types of intestinal protozoa are affecting people, such as Entamoeba histolytica, Giardia lamblia, Cryptosporidium parvum and Blastocystis hominis which then pass out through faeces of the infected person. A cross-sectional study was conducted in Kuantan, Pahang, Malaysia. The survey was collected from parents of school children in urban and peripheral area in Kuantan, Pahang, Malaysia. A total of 136 parents of school children were selected randomly from the primary schools at urban and peripheral for the study. Sixty-eight respondents from the urban primary school or UPS or “Sekolah Kebangsaan U” represent the parents of school children in urban area and sixty-eight respondents from the primary school or PPS or “Sekolah Kebangsaan P” represent the parents of school children in peripheral area. No significant difference was observed on knowledge, attitudes and practices of intestinal helminths and protozoa infection among parents from both areas. There was no significant difference in terms knowledge, attitudes and practices between parents from low income and high income. Awareness to the public regarding the intestinal parasites and good hygiene behavior were needed to expose the public about the intestinal helminth and protozoa infections.